Pengaruh Efektivitas dan Efisiensi Belanja Terhadap Kinerja Keuangan Pemerintah Daerah: (Studi di Kabupaten Pohuwato) - Fatma Kasim; Harun Blongkod (Journal of Applied Accounting, 2026)
This study aims to examine the influence of spending effectiveness and efficiency on the financial performance of local governments in Pohuwato Regency. The optimization of Regional Revenue and Expenditure Budget (APBD) management is a crucial factor in supporting development objectives and enhancing the quality of public services. In this regard, spending effectiveness and efficiency are considered key indicators in evaluating the success of regional financial management. This research employs a quantitative approach, with data collected through questionnaires distributed to 89 respondents consisting of local government officials and related stakeholders. Data analysis was conducted using the Structural Equation Modeling (SEM) method with the assistance of AMOS and SPSS software. The findings reveal that neither spending effectiveness nor spending efficiency has a significant effect on the financial performance of local governments. These results suggest that improvements in financial performance are not solely determined by effectiveness and efficiency in budget management, but are also influenced by other factors such as the quality of planning, supervision mechanisms, and the capacity of human resources in managing regional finances. Keywords: Spending Effectiveness, Spending Efficiency, Financial Performance, Local Government